Truncus bicaroticus: An underestimated anatomic variation. (11th November 2013) - Becker, Christoph; Csatari, Zoltan; Pfeiffer, Jens
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To illustrate that a truncus bicaroticus and an elongated truncus brachiocephalicus are underestimated anatomic variations; and to highlight the risk of injury of these vessel anomalies during routine surgical interventions. Data Source Report of a woman with long‐term ventilation who was planned for conventional surgical tracheostomy. Due to a strong pulsatile vessel crossing the cricoid cartilage, the procedure was stopped. Further diagnostics revealed anomalies of the supraaortic vessels, including a truncus bicaroticus. Conclusion Anomalies of supraaortic vessels are not rare and injuries may cause severe bleeding; therefore, we recommend performing a preoperative ultrasound, particularly before starting dilatative tracheostomy. Laryngoscope, 124:1141–1142, 2014